Analisis Bahan Pembelajaran Berbasis Konstektual Dalam Pendidikan Agama Islam (PAI) - Mafira Roza; Ahnaf Istiqlal Berutu; Indah Permata Sari (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study discusses the importance of contextual learning material analysis in Islamic Religious Education (PAI). Islamic Religious Education not only aims to transfer theoretical religious knowledge, but also to shape the character and morals of students through an approach that is relevant to everyday life. This study uses a library research method by analyzing various scientific literature related to the development of contextual PAI teaching materials. The results of the study show that contextual approaches such as Problem-Based Learning, Experiential Learning, and Project-Based Learning are able to increase student involvement and understanding of Islamic values. However, the implementation of this approach still faces challenges such as limited resources, lack of teacher training, and suboptimal technology integration. Nevertheless, the opportunity to develop contextual-based PAI teaching materials is very large, especially with the support of digital technology and innovative learning strategies. This article recommends the development of more interactive learning media and teacher training in implementing a contextual approach.